FUN GRAMMAR TEACHING - Nurlaila Kadariyah (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
It’s necessary to change our view that grammar is taught only as a set of rules making or changing of sentences structure, but grammar is a flexible frame that can be changed based on the communicative needs. Grammar also can be taught not only by giving explanation and exercises, but grammar can be taught by fun evaluation, games or outdoor activity, song, and poems. These are the ways to increase students’ motivation and interested in the material. Our class can be fun and interesting. The important thing in teaching and learning grammar is the students have experience to apply the grammar rules in a real communication and realistic context.